Detection of IMP-1 and OXA-24 Genes as Markers of Carbapenem Resistance in Acinetobacter baumannii Isolates - Rachel Lintang Putriku; Sinta Puspitasari; Vector Stephen Dewangga (Jurnal Biologi Tropis, 2026)
Nosocomial infections remain a major global health concern, particularly in developing countries, with Acinetobacter baumannii recognized as an important carbapenem-resistant pathogen. This study aimed to detect the presence of the OXA-24 and IMP-1 genes in carbapenem-resistant A. baumannii isolates obtained from a regional hospital in Surakarta. A descriptive observational study was conducted on 10 clinical isolates using polymerase chain reaction (PCR) analysis. DNA extraction was performed, followed by qualitative and quantitative DNA assessment, and PCR amplification targeting the OXA-24 gene (246 bp) and IMP-1 gene (172 bp). The results showed that no specific amplification bands corresponding to the expected target sizes were observed for either the OXA-24 or IMP-1 genes. It can be concluded that the OXA-24 and IMP-1 genes were not detected in the examined isolates. These findings suggest the possibility of alternative carbapenem-resistance mechanisms in the isolates and highlight the need for further studies involving optimization of primer design, PCR conditions, and DNA sequencing to confirm the genetic profile of resistance determinants.